A Structural Rearrangement of the Na+/K+-ATPase Traps Ouabain within the External Ion Permeation Pathway. Issue 6 (27th March 2015) - Sánchez-Rodríguez, Jorge E.; Khalili-Araghi, Fatemeh; Miranda, Pablo; Roux, Benoît; Holmgren, Miguel; Bezanilla, Francisco
Abstract: With the use of the energy of ATP hydrolysis, the Na + /K + -ATPase is able to transport across the cell membrane Na + and K + against their electrochemical gradients. The enzyme is strongly inhibited by ouabain and its derivatives, some that are therapeutically used for patients with heart failure (cardiotonic steroids). Using lanthanide resonance energy transfer, we trace here the conformational changes occurring on the external side of functional Na + /K + -ATPases induced by the binding of ouabain. Changes in donor/acceptor pair distances are mainly observed within the α subunit of the enzyme. To derive a structural model matching the experimental lanthanide resonance energy transfer distances measured with bound ouabain, we carried out molecular dynamics simulations with energy restraints applied simultaneously using a novel methodology with multiple non-interacting fragments. The restrained simulation, initiated from the X-ray structure of the E2 (2K + ) state, became strikingly similar to the X-ray structure of the sodium-bound state. The final model shows that ouabain is trapped within the external ion permeation pathway of the pump. Graphical abstract: Highlights: Proposed model of the ouabain bound conformation of a functional Na + /K + -ATPase. Ouabain binding changes distances at the external end of the α subunit helices. A molecular model shows ouabain trapped within the ion permeation pathway. The ouabain-bound model corresponds to a Na + -occluded state of the Na + /K + -ATPase.